Effect of transverse gradient extrusion process on texture and mechanical properties of Mg–3Al–1Zn alloy sheets - Jun Xu; Jun Zhao; Bin Jiang; Xudong Chen; Qingshan Yang; Nan Zhou; Weiwen Zhang; Kaihong Zheng; Fusheng Pan (Journal of Materials Research and Technology, 2023)
Transverse gradient extrusion (TGE) processes with different die inclined angles of 15°, 30°, 45°and 60° were used to produce Mg–3Al–1Zn sheets, thereby tailoring texture and mechanical properties of Mg alloy sheets. Microstructure, deformation texture and final mechanical properties of the obtained sheets were detected and discussed. Furthermore, the rheological behavior of Mg alloys during extrusion was analyzed by finite element method. As the TGE die inclined angle changed, the flow velocity along the transverse direction (TD) and effective strain difference along extrusion direction (ED) were changed during extrusion, and therefore the microstructure and texture of extruded sheets are altered. With increase of TGE die inclined angles, fine grain size and uniform microstructure were obtained. The base poles of most grains for the extruded sheets gradually deviate from normal direction (ND) to ED at center region and inclined from ED to TD at 1/4 edge region. A large elongation of 33.9 % and a low yield stress of 125 MPa can be obtained in the TGE-45 sheet.